(untitled) (Journal of Asian Development Studies, 2018)
Despite the growing recognition of the role of indigenous communities in regulatory environmental impact assessment (EIA) internationally, practice seems not to have reached its full potential. At present, it could be argued that the consultation of indigenous communities in EIA processes is still largely seen as an appeasement mechanism than a credible and transparent opportunity to achieve environmentally responsible development choices. This paper presents two cases – Bipole III Transmission Line Project (Manitoba, Canada) and Bui Hydropower Project (Ghana) – to represent practice in the developed and developing nations respectively, where indigenous communities are to shoulder the environmental burdens of hydropower projects. We observe in both cases the unidirectional nature of consultation, where proponents tolerate rather than incorporate local perceptions into the EIA studies. We conclude that current practices offer little difference between the developed and developing nations in approaches to indigenous communities’ consultation in project EIAs, thereby prompting the need to advance discourse in this area.